Grain, fodder and residue management - Tedla, A.; Mohamed-Saleem, M.A.; Mamo, T.; Tadesse, A.; Duffera, M. (International Livestock Centre for Africa, 1993)
Although this document is intended to report research on Vertisols, livestock do not respect this boundary as they graze communal land. Hence a general situation of the available feed resources in the highlands is also highlighted which is followed by specific efforts of collaborative partners of the Joint Vertisol Project. In this paper the improvement of native pasture; crop residues as main animal feed and possibilities for increased production; fodder improvement in the Ethiopian highland Vertisols, traditional management and cropping patterns and calendar of highland Vertisols are discussed. This paper examines the possibility of early planting of improved wheat varieties on drained Vertisols as Opposed to the traditional late planting, towards the end of the rainy season, and evaluates wheat varieties in terms of grain and straw yields and quality across highland drained Vertisols sites.